DNA Binding and Cleavage, Stopped-Flow Kinetic, Mechanistic, and Molecular Docking Studies of Cationic Ruthenium(II) Nitrosyl Complexes Containing "NS4" Core - Shereef, Hadeer A.; Moemen, Yasmine S.; Elshami, Fawzia I.; El-Nahas, Ahmed M.; Shaban, Shaban Y.; van Eldik, Rudi (Molecules, 2023)
This work aimed to evaluate in vitro DNA binding mechanistically of cationic nitrosyl ruthenium complex [RuNOTSP]+ and its ligand (TSPH2) in detail, correlate the findings with cleavage activity, and draw conclusions about the impact of the metal center. Theoretical studies were performed for [RuNOTSP]+, TSPH2, and its anion TSP-2 using DFT/B3LYP theory to calculate optimized energy, binding energy, and chemical reactivity. Since nearly all medications function by attaching to a particular protein or DNA, the in vitro calf thymus DNA (ctDNA) binding studies of [RuNOTSP]+ and TSPH2 with ctDNA were examined mechanistically using a variety of biophysical techniques. Fluorescence experiments showed that both compounds effectively bind to ctDNA through intercalative/electrostatic interactions via the DNA helix's phosphate backbone. The intrinsic binding constants (Kb), (2.4 ± 0.2) × 105 M-1 ([RuNOTSP]+) and (1.9 ± 0.3) × 105 M-1 (TSPH2), as well as the enhancement dynamic constants (KD), (3.3 ± 0.3) × 104 M-1 ([RuNOTSP]+) and (2.6 ± 0.2) × 104 M-1 (TSPH2), reveal that [RuNOTSP]+ has a greater binding propensity for DNA compared to TSPH2. Stopped-flow investigations showed that both [RuNOTSP]+ and TSPH2 bind through two reversible steps: a fast second-order binding, followed by a slow first-order isomerization reaction via a static quenching mechanism. For the first and second steps of [RuNOTSP]+ and TSPH2, the detailed binding parameters were established. The total binding constants for [RuNOTSP]+ (Ka = 43.7 M-1, Kd = 2.3 × 10-2 M-1, ΔG0 = -36.6 kJ mol-1) and TSPH2 (Ka = 15.1 M-1, Kd = 66 × 10-2 M, ΔG0 = -19 kJ mol-1) revealed that the relative reactivity is approximately ([RuNOTSP]+)/(TSPH2) = 3/1. The significantly negative ΔG0 values are consistent with a spontaneous binding reaction to both [RuNOTSP]+ and TSPH2, with the former being very favorable. The findings showed that the Ru(II) center had an effect on the reaction rate but not on the mechanism and that the cationic [RuNOTSP]+ was a more highly effective DNA binder than the ligand TSPH2 via strong electrostatic interaction with the phosphate end of DNA. Because of its higher DNA binding affinity, cationic [RuNOTSP]+ demonstrated higher cleavage efficiency towards the minor groove of pBR322 DNA via the hydrolytic pathway than TSPH2, revealing the synergy effect of TSPH2 in the form of the complex. Furthermore, the mode of interaction of both compounds with ctDNA has also been supported by molecular docking.
CRIS-Team Scopus Importer:2023-04-21
Keywords: binding interaction; DNA; kinetic investigation; molecular docking; reaction mechanism; ruthenium nitrosyl complexes